ASSESSMENT OF MOTHER'S LEVEL OF KNOWLEDGE ON WHO DANGER SIGNS IN NEONATES-A HOSPITAL BASED SURVEY - Ullah, Saffi; Malik, Farhat Rehana; Gul, Anum (Journal of Postgraduate Medical Institute, 2020)
Objective: To assess maternal knowledge of World Health Organization (WHO) recognized neonatal danger signs and its association with maternal demographic characteristics. Methodology: This descriptive study was conducted in pediatric unit of Kuwait Teaching Hospital Peshawar among 100 post-natal mothers. A pre structured questionnaire was administered to collect data. WHO recognized neonatal danger signs included; poor suckling, convulsions, increased respiratory rate, difficulty in breathing, fever, hypothermia, lethargy, jaundice and local infection. The total number of nine correct spontaneous responses was scored excellent, 7 as good, 5 as average, 3 as fair and 0 as poor knowledge. Data were analyzed with SPSS version 20 with computation of descriptive statistics and Chi square with significance level at 0.05. Results: Mean maternal age was 26.42 years with SD as 6.044 (95% CI; 25.32- 27.57). Excellent knowledge of mothers was found in poor suckling (87.1%), convulsions (89.1%), fast breathing (81.2%) and difficulty in breathing (86.1%). Moderate knowledge was found for fever (72.3%), lethargy (67.3%) and local infection (63.4%). Poor knowledge was exhibited in hypothermia (44.6%) and jaundice (42.6%). P value was significant for difficult breathing (0.03) and lethargy (0.04). Only age of mothers was found to be significant for fever (0.022) and jaundice (0.030). Overall 31% of the mothers had excellent, 16% very good, 33% average, 16% fair and 5% poor knowledge of danger signs. Conclusion: The study revealed excellent maternal knowledge in four, moderate in three and poor in two neonatal danger signs. Significant demographic variable was age of mothers.